2016
DOI: 10.18331/brj2016.3.3.7
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced ethanol and glucosamine production from rice husk by NAOH pretreatment and fermentation by fungus Mucor hiemalis

Abstract: Please cite this article as: Omidvar M., Karimi K., Mohammadi M. Enhanced ethanol and glucosamine production from rice husk by NAOH pretreatments and fermentation by fungus Mucor hiemalis. Biofuel Research Journal 11 (2016) 475-481. DOI: 10.18331/BRJ2016.3.3.7 Biofuel Research Journal 11 (2016) HIGHLIGHTS Ethanol production from rice husk using Mucor hiemalis was investigated. The maximum ethanol production yield of 86.7%was observed after pretreatment with 2.6 M NaOH at 67°C for 150 min.A highly va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…From this study, 90mins pretreatment time with 2% NaOH was found to be more effective for pretreatment of rice bran and maximum ethanol yield was obtained. Omidvar et al, [16] reported 2.6M NaOH at 67°C for 150 minas optimum pretreatment condition of rice husk in their study of enhanced ethanol and glucosamine production from rice husk by NaOH pretreatment and fermentation by Mucor hiemalis. However the effect of alkaline pretreatment method depends on lignin content of lignocellulosic biomass McMillan [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From this study, 90mins pretreatment time with 2% NaOH was found to be more effective for pretreatment of rice bran and maximum ethanol yield was obtained. Omidvar et al, [16] reported 2.6M NaOH at 67°C for 150 minas optimum pretreatment condition of rice husk in their study of enhanced ethanol and glucosamine production from rice husk by NaOH pretreatment and fermentation by Mucor hiemalis. However the effect of alkaline pretreatment method depends on lignin content of lignocellulosic biomass McMillan [24].…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneous saccharification and fermentation that is, hydroylosis and fementation was carried out in same vessel according to the method described by Omidvar et al, [16]…”
Section: Simultaneous Saccharification and Fermentation With S Cerevmentioning
confidence: 99%
See 1 more Smart Citation
“…Yoo et al subjected the substrate with ammonia treatment before applying hot water pretreatment. Omidvar et al pretreated rice husk at 0°C to 100°C, with NaOH concentration 1 to 3 M for the time of 30 to 180 minutes. Further on simulators saccharification and fermentation it produced 86.7% ethanol produce.…”
Section: Organic Solventsmentioning
confidence: 99%
“…For example, Brazil, with its experience of more than 40 years in bioethanol production at the commercial scale, depends on sugarcane molasses (Lopes et al, 2016). In Asian and African countries, rice straw (Singh et al, 2017) and rice husks (Omidvar et al, 2016) are the locally available feedstocks for bioethanol production. The waste generated from oil palm tree is the principal source for bioethanol production in countries such as Indonesia, Thailand, and Malaysia (Shahirah et al, 2015).…”
Section: Introductionmentioning
confidence: 99%